Working landscapes need at least 20% native habitat - Garibaldi, Lucas A.; Oddi, Facundo J.; Miguez, Fernando E.; Bartomeus, Ignasi; Orr, Michael C.; Jobbágy, Esteban G.; Kremen, Claire; Schulte, Lisa A.; Hughes, Alice C.; Bagnato, Camilo; Abramson, Guillermo; Bridgewater, Peter; et al. (Conservation letters, 2021)
International agreements aim to conserve 17% of Earth's land area by 2020 but include no area‐based conservation targets within the working landscapes that support human needs through farming, ranching, and forestry. Through a review of country‐level legislation, we found that just 38% of countries have minimum area requirements for conserving native habitats within working landscapes. We argue for increasing native habitats to at least 20% of working landscape area where it is below this minimum. Such target has benefits for food security, nature's contributions to people, and the connectivity and effectiveness of protected area networks in biomes in which protected areas are underrepresented. We also argue for maintaining native habitat at higher levels where it currently exceeds the 20% minimum, and performed a literature review that shows that even more than 50% native habitat restoration is needed in particular landscapes. The post‐2020 Global Biodiversity Framework is an opportune moment to include a minimum habitat restoration target for working landscapes that contributes to, but does not compete with, initiatives for expanding protected areas, the UN Decade on Ecosystem Restoration (2021–2030) and the UN Sustainable Development Goals.